2011
DOI: 10.1080/10401334.2011.561190
|View full text |Cite
|
Sign up to set email alerts
|

Resident Sign-Out and Patient Hand-Offs: Opportunities for Improvement

Abstract: We found variability in the content and organization of interns' sign-out, possibly reflecting a lack of instruction and supervision. Standardization of sign-out content, and education on good sign-out skills are increasingly important as patient hand-offs become more frequent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 18 publications
(14 reference statements)
2
30
0
Order By: Relevance
“…Faculty oversight, review of handoff content, and feedback resulted in statistically significant content error reductions and correction of content that could have led to a serious patient safety issue; therefore, we recommend the 17,29,33,53 N Persistence of inaccurate data 19,29,33,34,37,44 N Clinician resistance to change 31,46,47,50 N Perception that the handoff tool might interfere with direct physician communication 26,40,41 N Duplication of work or more work 17,32 N Errors created by free-text entry 54 use of faculty oversight and real-time feedback of resident handoffs in medical education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Faculty oversight, review of handoff content, and feedback resulted in statistically significant content error reductions and correction of content that could have led to a serious patient safety issue; therefore, we recommend the 17,29,33,53 N Persistence of inaccurate data 19,29,33,34,37,44 N Clinician resistance to change 31,46,47,50 N Perception that the handoff tool might interfere with direct physician communication 26,40,41 N Duplication of work or more work 17,32 N Errors created by free-text entry 54 use of faculty oversight and real-time feedback of resident handoffs in medical education.…”
Section: Discussionmentioning
confidence: 99%
“…26 An observational study found that that only 11% included ''Do Not Resuscitate'' or advance directive information, and only 50% of successive handoffs were updated daily. 53 Another study found that 96% of electronic handoffs were updated within 24 hours, 51 while a third study found an increase in the documentation of 12 of 16 specific data elements studied, a decrease in 3 elements, and no difference in 1 element. 48 Three studies noted that an electronic handoff tool should include free-text options for current anticipatory guidance and comments, 25,35,48 and another reported that users need to be encouraged to be vigilant in revising and updating free-text sections.…”
Section: Process Measuresmentioning
confidence: 99%
“…search, we identified 26 articles (32 tools) published between January 1, 2008, and May 13, 2015, that focused on inpatient handoff feedback or assessment tools (FIGURE). Of these articles, 3 were relevant to feedback only, 2 7 , 2 9 , 34 8 to assessment only, 15,18,19,21,23,31,33,35 and 15 to feedback and assessment (TABLES 1 and 2). 16,17,20,22,[24][25][26]28,30,32,[36][37][38][39][40] Copies of some tools are available from the authors on request.…”
Section: Types Of Data Reportedmentioning
confidence: 99%
“…15,17,24,28,30,32,33,[36][37][38][39] Other study designs inc l u d e d va li d i t y e vi d e n ce o n l y (6 o f 2 6 , 23%) 19,21,26,29,31,35 ; randomized control trial (2 of 26, 7.7%) 16,25 ; posttest study (2 of 26, 7.7%) 20,40 ; observational study (2 of 26, 7.7%) 18,23 ; and matched group design with random assignment to control and trained groups (1 of 26, 3.8%). 22 The studies included the specialties of internal medicine (12 of 26, 46%) 15,16,18,19,[23][24][25][26][27]31,34,37 ; pediatrics (3 of 26, 12%) 33,38,39 ; pediatric cardiac critical care (1 of 26, 3.8%) 21 ; surgery (1 of 26, 3.8%) 29 ; emergency medicine (1 of 26, 3.8%) 36 ; and gastroenterology (1 of 26, 3.8%). 40 Several of the studies used participants from more than 1 specialty (7 of 26, 27%).…”
Section: Types Of Data Reportedmentioning
confidence: 99%
See 1 more Smart Citation